DIFFERENTIATION IN HETEROGENEOUS FOREIGN LANGUAGE CLASSES - Margevica-Grinberga, Ieva; Rektina, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The article covers the issue of how to teach foreign languages most effectively in heterogeneous classes. Such classes have occurred in most schools and classrooms in recent years. There is an exploration of the latest pedagogical literature and research of the developments and practices in differentiation for mixed classes reviewed in the article. In addition to the theoretical analysis of the literature, practical recommendations from meta-analysis studies and pedagogical specialists are provided. The practical suggestions cover the subsequent steps (e.g., pre-assessment of the students, diversity of the content in the classroom, different learning methods, differentiating of learning outcomes, etc.), that should be implemented in heterogeneous class groups in order to maximize the effectiveness of learning of a foreign language, but the practical approach will be reviewed more widely on the further articles. The article also covers research-based information about the barriers in foreign language teaching to find the solution to the addressed issues. As the respective barriers, the following are named – lack of specific teacher education regarding the mentioned matters and lack of implementing the particular methods in mixed ability groups.